2013
DOI: 10.1111/psyp.12037
|View full text |Cite
|
Sign up to set email alerts
|

A parietal‐to‐frontal shift in the P300 is associated with compensation of tactile discrimination deficits in late middle‐aged adults

Abstract: Tactile perception declines with age on both behavioral and neurophysiological levels. Less well understood is how neurophysiological changes relate to tactile discrimination performance in middle adulthood. A tactile discrimination task was conducted while ERPs were measured in three groups of healthy adults aged 20 to 66 years. Accuracy was lowest in late middle adulthood (56-66 years) while somatosensory ERP components (P50, N70, P100, N140) were comparable across age groups. The cognitive P300 revealed age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 86 publications
2
32
1
Order By: Relevance
“…So it seems that older adults received a stable somatosensory input but impaired central processing. Similar to that described for tactile discrimination tasks, 51 age-related changes in pharyngeal sensitivity may not be the result of an intrinsic peripheral alteration but rather the strong affectation in cognitive processing at a cortical level. An apparent time-to-peak decrease accompanied by decreased amplitude in the earlier components (N1 and P1) may reflect less recruitment of cortical neurons due to a decrease in afferent inputs from the pharyngeal wall, while an apparent time-to-peak increase accompanied by decreased amplitude in the later components (N2 and P2) may reflect less recruitment of cortical neurons due to a disruption of the connection within the cortex.…”
Section: Age-related Changes Of the Pharyngeal Sensory Functionsupporting
confidence: 58%
See 1 more Smart Citation
“…So it seems that older adults received a stable somatosensory input but impaired central processing. Similar to that described for tactile discrimination tasks, 51 age-related changes in pharyngeal sensitivity may not be the result of an intrinsic peripheral alteration but rather the strong affectation in cognitive processing at a cortical level. An apparent time-to-peak decrease accompanied by decreased amplitude in the earlier components (N1 and P1) may reflect less recruitment of cortical neurons due to a decrease in afferent inputs from the pharyngeal wall, while an apparent time-to-peak increase accompanied by decreased amplitude in the later components (N2 and P2) may reflect less recruitment of cortical neurons due to a disruption of the connection within the cortex.…”
Section: Age-related Changes Of the Pharyngeal Sensory Functionsupporting
confidence: 58%
“…P300 has been demonstrated to be smaller across a variety of tasks, has a longer latency, and has a more frontal scalp distribution in older relative to younger adults . This phenomenon has diverse functional interpretation, from being a marker of an age‐related reduction in processing efficiency and difficulty in recruiting specialized neural mechanisms to a good and efficient compensatory mechanism …”
Section: Discussionmentioning
confidence: 99%
“…P300 latency relates to the relative timing of stimulus evaluation processes (Kutas et al ., ; McCarthy & Donchin, ; Polich, ; Kok, ). Recently, we showed that age‐related decline in tactile perception is reflected in changed P300 amplitude distribution (Reuter et al ., ). By use of oddball paradigms, it has been shown that discrimination ability influences P300 amplitudes in such a way that the easier the stimuli are to be differentiated, the larger P300 is for the deviant stimuli (Polich, , ).…”
Section: Introductionmentioning
confidence: 97%
“…Reduced tactile perception, e.g. in older adults, presumably affects hand functioning and reduces manual dexterity (Dinse et al ., , ; Bowden & McNulty, ; Reuter et al ., , ; Vieluf et al ., ). However, it can also be improved by tactile short‐term interventions, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation